UJI EKSPERIMENTAL PROSES PLASTIC WELDING TERHADAP PERLAKUAN PRE HEATING KONSTRUKSI HDPE KAPAL IKAN - Samuel Febriary Khristyson; Mohammad Ridwan; Luthfi Afrizal; Pawesti Wulan (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2023)
Fishing boats have a construction design that generally uses wood materials. The cost of making fishing boats made of wood varies and the value depends on the type of construction design. The difficulty of recovering wood from this plant makes the need for alternative materials. HDPE plastic or polyethylene (PE) and polypropylene (PP) High Density Polyethylene (HDPE) which has good properties, such as corrosion resistance and light weight, is still one of the most widely adopted materials for the realization of an alternative construction. The purpose of this study was to determine and analyze the effect of temperature on pre heating on the HDPE plastic welding process. The method used is an experiment where the specimen is made using HDPE material according to the ASTM D638 standard. The welding process uses temperature variations between 4000 - 4500 C. The results show the highest value of tensile testing at pre heating 450o C is 18.2 MPa while the lowest value at pre heating 410o C is 13.7 MPa, with an average elongation of 136.8mm . This concludes that there is an effect of preheating on the plastic welding process with HDPE material.